First identification of non-human stencil hands at Wadi Sūra II (Egypt): A morphometric study for new insights into rock art symbolism. (April 2016) - Honoré, Emmanuelle; Rakza, Thameur; Senut, Brigitte; Deruelle, Philippe; Pouydebat, Emmanuelle
Abstract: In the Libyan Desert, Wadi Sūra II shelter hosts numerous stencil paintings believed to date to the Early and Mid-Holocene. Tiny hands have previously been considered to belong to human babies. We challenge this identification, having conducted a morphometric study to compare the archaeological material with samples of hands of babies born at term and pre-term at the neonatal unit of the CHRU Jeanne de Flandre (Lille, France). The results show that the rock art small hands differ significantly in size, proportions and morphology from human hands. Potential biases between the different samples were quantified, but their average range cannot explain the observed differences. Evidence suggest that the hand stencils belong to an animal, most probably a reptile. The identification of non-human pentadactyl hand stencils is unique in the field of rock art and raises new perspectives for understanding the rock art at Wadi Sūra, and the behaviour and symbolic universe of the populations who made it. Highlights: We challenge the identification of the small hand stencils of Wadi Sūra II shelter. The morphometric study focuses on the size, proportions and morphology of the hands. The comparison with reference samples shows significant difference from human hands. Evidence suggests that stencils are most probably made from reptile forefeet.